1989
DOI: 10.1161/01.cir.80.5.1320
|View full text |Cite
|
Sign up to set email alerts
|

A prospective study of nutritional factors and hypertension among US women.

Abstract: The relation of various nutritional factors with hypertension was examined prospectively among 58,218 predominantly white US female registered nurses, aged 34-59 years. In 1980, all women completed an independently validated dietary questionnaire. During 4 years of follow-up, 3,275 women reported a diagnosis of hypertension; the validity of the self-report was shown in a subsample. Age, relative weight, and alcohol consumption were the strongest predictors for the development of hypertension. Dietary calcium … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
116
0
5

Year Published

1997
1997
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 248 publications
(125 citation statements)
references
References 49 publications
4
116
0
5
Order By: Relevance
“…In women, there was no observed risk increase for consumption of 1 or 2 drinks/day in comparison with abstainers, and an increased risk beyond this level with a pooled RR=1.42 (95% CI, 1.22–1.66; I 2 =88%) for consumption of 3 or more drinks per day (Figure 3 and Figure S3). Because we included 2 studies from the Nurses’ Health Study42, 45 with different follow‐up periods of the same participants, we ran a sensitivity analysis including only 1 42. The results compared to Figure 3 were almost identical (1–2 drinks/day: pooled RR=0.95; 95% CI, 0.88–1.03).…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…In women, there was no observed risk increase for consumption of 1 or 2 drinks/day in comparison with abstainers, and an increased risk beyond this level with a pooled RR=1.42 (95% CI, 1.22–1.66; I 2 =88%) for consumption of 3 or more drinks per day (Figure 3 and Figure S3). Because we included 2 studies from the Nurses’ Health Study42, 45 with different follow‐up periods of the same participants, we ran a sensitivity analysis including only 1 42. The results compared to Figure 3 were almost identical (1–2 drinks/day: pooled RR=0.95; 95% CI, 0.88–1.03).…”
Section: Resultsmentioning
confidence: 96%
“…Nine reports were from the United States,22, 23, 24, 42, 43, 44, 45, 46, 47 4 from Japan,48, 49, 50, 51 2 from China,52, 53 and 1 each from Germany,54 South Korea,55 Finland,56 Turkey,57 and Thailand58 (Table). Several reports from the Nurses’ Health Study42, 44, 45, 46 were included, but any 1 case of incident hypertension was included only once in any particular analysis. Overall, data from 361 254 participants (125 907 men and 235 347 women) and 90 160 incident cases of hypertension (32 426 men and 57 734 women) were analyzed.…”
Section: Resultsmentioning
confidence: 99%
“…1±5 Overweight and obesity are well known independent risk factors for increased mortality, 6±8 and for several chronic disorders such as musculoskeletal 9,10 and cardiovascular diseases, 11±14 hypertension, 15,16 and diabetes. 17±20 Although there appears to be a graded association between body mass and the disease risk, a clinically signi®cant risk for some of these states is associated with a body mass index (BMI) value of approximately 26 or more and with a body mass gain of at least 5 kg during a 10 y or longer follow-up period.…”
Section: Introductionmentioning
confidence: 99%
“…20 In the prospective Nurses' Health Study, dietary fatty acids showed no association with the 4-year incidence of hypertension. 21 An increase in linoleic acid intake has been shown to reduce BP both in combination with reduced fat intake [22][23][24][25] and with unchanged fat intake. [26][27][28][29] In contrast to these findings, several studies have failed to show an effect on BP by increased intake of linoleic acid.…”
Section: Introductionmentioning
confidence: 99%